Management of Pseudohypoparathyroidism Type 1a during Pregnancy and Labor: A Case Report. (24th June 2012) - Singh, Anju; Agarwal, Neelam; Chopra, Seema; Sikka, Pooja; Suri, Vanita; Kumar, Bhupesh; Dutta, Pinaki
Abstract : Pseudohypoparathyroidism is rare during pregnancy and poses multiple challenges related to its diagnosis and management during pregnancy. We hereby report a case of a young woman who was diagnosed to have type 1a pseudohypoparathyroidism. She was managed by multidisciplinary team and had good maternal and perinatal outcome. Management-related issues are discussed here in detail.